Pull out characteristics of soil nails in Pahang / Damanhuri Jamalludin ...[et al.] - Jamalludin, Damanhuri; Ahmad, Mohd Farid; Mohd Salleh, Samsuri; Md. Issa, Ahmad Kamal; Mohd Ali, Siti Norizan (Universiti Teknologi MARA, Perlis, 2010)
A total of 45 locations of slope failures occurred along Jalan Baru Gap to Fraser Hill, Pahang. Of the 45 locations of slope failures, only 31 locations were repaired using soil nails. At each location, only one pull out test was carried out. This study involved the results of the pull out tests at all the 31 locations and the results were obtained from Public Works Department, K.L. The maximum pull out load during the test was 90 kN and the displacement at 90 kN load must be less than 10mm for the test to be considered satisfy the specifications. The main purpose of this study is to determine the characteristics of the pull out test on soil nail and the interaction between the soil nail and the soil.